2020
DOI: 10.1101/2020.06.30.20143578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

APOE4 Copy Number-Dependent Proteomic changes in the Cerebrospinal Fluid

Abstract: Background: APOE4 has been hypothesized to increase Alzheimer's disease risk by increasing neuroinflammation, though the specific neuroinflammatory pathways involved are unclear. Objectives: To characterize CSF proteomic changes as a function of APOE4 copy number. Methods: We analyzed targeted proteomic data obtained on ADNI CSF samples using a linear regression model adjusting for age, sex, and APOE4 copy number, and a second linear model also adjusting for AD clinical status. False Discovery Rate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 82 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…Here, MDH1 was observed to increase with amyloid and tau pathology. ALDOA has been previously positively associated with CSF tau levels 79 , as was the case here, and also associated with the APOE ε4 allele 96 . Glucose metabolism, which is the major source of energy for the brain, has long been known to show signs of dysfunction in AD even before the emergence of symptoms [97][98][99][100][101] .…”
Section: Discussionsupporting
confidence: 82%
“…Here, MDH1 was observed to increase with amyloid and tau pathology. ALDOA has been previously positively associated with CSF tau levels 79 , as was the case here, and also associated with the APOE ε4 allele 96 . Glucose metabolism, which is the major source of energy for the brain, has long been known to show signs of dysfunction in AD even before the emergence of symptoms [97][98][99][100][101] .…”
Section: Discussionsupporting
confidence: 82%
“…CD33 controls the microglial activation state, turning microglia from housekeepers that clear amyloid into killers that destroy neurons [54][55][56][57]. Its association with AD is supported by some [10,16,[58][59][60][61], but not all [9,28] genetic studies. The CD33 rs3865444(C) risk allele was reported to be associated with greater cell surface expression of CD33 in monocytes, accumulation of amyloid pathology and increased numbers of activated human microglia [62], and increased CD33 expression was also observed in microglial cells in the AD brain [56].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we observed that elevated blood CRP levels increased the risk of AD for people carrying the APOE ε4 allele [6][7][8]. In addition, low CSF CRP was the biomarker most closely associated with the APOE ε4 copy number, not high CSF CRP levels [9]. We hypothesized that CRP, as a key inflammatory element, could modulate the impact of other genetic variants on AD risk, especially variants in gene loci involved in proinflammation.…”
Section: Introductionmentioning
confidence: 95%
“…Accumulating evidence has demonstrated a significant relationship between APOE and innate immune function in AD (74, 75), but the relationship between APOE4 and adaptive immunity is less understood. Recent work has found that adaptive immunity is dysregulated in APOE4 -carriers, with decreased abundance of C-reactive protein (CRP) relative to APOE3 subjects, as assessed in CSF (76) and following both acute (77) and chronic (78) measurements of CRP in blood serum. Chronically low levels of CRP were also associated with accelerated AD onset (78).…”
Section: Discussionmentioning
confidence: 99%